Anti-Granulocyte-Macrophage Colony-Stimulating Factor Autoantibodies Are a Risk Factor for Central Nervous System Infection by Cryptococcus gattii in Otherwise Immunocompetent Patients - Tomomi Saijo (American Society for Microbiology, 2014)
ABSTRACT Cryptococcosis is caused by either Cryptococcus neoformans or C. gattii. While cryptococcal meningoencephalitis is caused mostly by C. neoformans in immunocompromised patients, the risk factors remain unclear for patients with no known immune defect. Recently, anti-granulocyte-macrophage colony-stimulating factor (GM-CSF) autoantibodies were detected in the plasma of seven “immunocompetent” cryptococcosis patients, and the cryptococcal strains from these patients were reported as C. neoformans (three strains), C. gattii (one strain), and Cryptococcus (three strains not identified to the species level). We identified all three strains that had not been identified to the species level as C. gattii. Notably, the three strains that were reported as C. neoformans but were unavailable for species confirmation originated from Sothern California and Thailand where C. gattii is endemic. Most clinical laboratories designate C. neoformans without distinguishing between the two species; hence, these three strains could have been C. gattii. Since C. gattii infects more immunocompetent patients than C. neoformans, we pursued the possibility that this antibody may be more prevalent in patients infected with C. gattii than in those infected with C. neoformans. We screened the plasma of 20 healthy controls and 30 “immunocompetent” patients with cryptococcal meningoencephalitis from China and Australia (multiple ethnicities). Anti-GM-CSF autoantibodies were detected only in the plasma of seven patients infected by C. gattii and one healthy volunteer and in none infected by C. neoformans. While plasma from these C. gattii patients completely prevented GM-CSF-induced p-STAT5 in normal human peripheral blood mononuclear cells (PBMCs), plasma from one healthy volunteer positive for anti-GM-CSF autoantibodies caused only partial blockage. Our results suggest that anti-GM-CSF autoantibodies may predispose otherwise immunocompetent individuals to meningoencephalitis caused by C. gattii but not necessarily to that caused by C. neoformans. IMPORTANCE Cryptococcal meningoencephalitis is the most serious central nervous system (CNS) infection caused by Cryptococcus neoformans or C. gattii. Cryptococcus primarily infects immunocopromised patients but is also sporadically encountered in otherwise “immunocompetent” patients with no known risk. In a recent study, anti-GM-CSF autoantibodies were detected in the plasma of seven otherwise immunocompetent patients with cryptococcal meningoencephalitis. Four of seven (57%) cryptococcal isolates from these patients were identified as C. gattii, while three strains were unavailable for species confirmation. We collected plasma from 30 otherwise healthy patients with CNS cryptococcosis in China and Australia (multiethnic) and analyzed the samples for the presence of anti-GM-CSF autoantibodies. The results suggest that anti-GM-CSF autoantibodies are a risk factor for CNS infection by C. gattii but not C. neoformans. GM-CSF may have a specific role in host defense against C. gattii, thereby elevating the importance of determining the level of anti-GM-CSF autoantibodies which can impact clinical management.